Qualitative Analysis of Science Question Paper of Class X Board Examination - Sharma, R.K.; Kamath, Asha KVD (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Examinations, to assess students’ learning, are an important aspect of curriculum implementation, as it affects what the students learn and the way they learn. Ideally, examination process is meant to guide teaching-learning process and hence considered supportive to it. Many tools and techniques have been developed to assess the learning of learners. Some of them are- written tests, oral tests, practicals, projects, interviews etc. However, in Science learning assessment process, the activities/experiments/technological modules within the textbook should also be assessed for Class X Board Examinations. The theoretical science paper for examinations for the Class X Board examinations should have carefully designed experiment/technology-based questions, questions testing critical understanding and ability to solve problems. In view of the above, an attempt has been made in the present study to analyze the Science question paper of class X (2015) of Rajasthan Board of Secondary Education